PERAN ORANG TUA DALAM MEMBIMBING ANAK MENGHADAPI ERA DIGITAL DAN GLOBALISASI - Masganti Sit; Almira Esa Nailah; Nur’aini Nur’aini; Yessy Prisilla Sillpana (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
In the digital era, human life has changed significantly, especially concerning the use of information and communication technology. This article discusses how parents can educate their children to navigate the digital era and the most effective methods to protect them from its threats. In today’s technological age, it is crucial for parents to understand the proper ways to educate their children. For this research, the investigator chose a more humane and personal data collection method. The study was conducted through direct interviews and semi-structured documentation with parents who are genuinely involved in their daily lives. The objective is to gather stories and individual perspectives on parental approaches to child education in this era of globalization and digitalization, characterized by numerous electronic devices and the internet. In the digital era, parents may face challenges in guiding their children, such as over-reliance on devices and disobedience to parental advice. Considering the many negative effects of technology use, parents are expected to teach their children how to use it properly.